A novel and facile synthesis of 3, 5-Disubstituted isothiozoles under metal free conditions using acetophenones and dithioesters. Issue 17 (1st September 2020) - Nagaraju, Chaithra; Ashok, Swarup Hassan; Shamanth, Sadashivamurthy; Nagarakere, Sandhya C.; Sunilkumar, Makanahalli P.; Subbegowda, Rangappa Kanchugarakoppal; Mantelingu, Kempegowda
Abstract: A facile and conveniently simple new protocol is devised for the synthesis of 3, 5-disubstituted and annulated isothiozoles under transition metal and catalyst free conditions utilizing easily available acetophenones, dithioesters and NH4 OAc. This strategy involves C=O and C=S functionalization via sequential imine formation followed by intra molecular cyclization and aerial oxidation forming consecutive C−N and S−N bonds respectively in one pot. This protocol offers a low cost, user friendly, straight forward and widely applicable approach to 3, 5-disubstituted isothiazoles. Graphical Abstract: